Posted by **stanley** on Sunday, February 24, 2013 at 8:07am.

proof thise for me. nCr=nCr-r

2) nCr+nCr+1=n+1Crr+1

## Answer This Question

## Related Questions

- math - prove:1) nCr=nCr-r 2) nCr+nCr+1=n+1Crr+1
- MATH - if nCr+2*nCr=nCr4+1*nCr-1
- Math - nPr=6720 and nCr=56, then the value if r is___?
- statistics - Are these using nCr? If not what formula do I use? P(20,x,23)= P(x....
- math - express each of the following expressions in the form nPr or in the form ...
- Algebra /Happy Holiday Everyone - Evaluate the Expression This is combination ...
- math - Use the formula nCr to solve Of the 100 people in the U.S. senate, 18 ...
- Math - i have my final tomorrow and this question was on my review? im having ...
- m ath - Use the formula nCr to solve Of the 100 people in the U.S. senate, 18 ...
- Pre Calc - The symbol nCr, rea "n choose r" or "the number of combinations of n ...

More Related Questions